2021
DOI: 10.1021/acssuschemeng.0c07217
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent Formed by Imidazolium Cyanopyrrolide and Ethylene Glycol for Reactive CO2 Separations

Abstract: Solvents made from a reactive ionic liquid, with an imidazolium cation and pyrrolide anion, and ethylene glycol at a wide compositional range were studied for separations of CO 2 at low partial pressures (≪0.1 bar up to 1 bar). Thermal analysis and measurements of viscosity and density show compacting of the liquid upon mixing with enhanced stability achieved by hydrogen bonding. A detailed mechanistic study was performed by IR, quantitative NMR, and ab initio calculations that show significant CO 2 absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 36 publications
(72 reference statements)
15
85
0
Order By: Relevance
“…The 1 H- 13 C HMBC suggested that the carbon C-4 should be the carbonyl carbon of the carbonate formed by CO 2 and EG. The carbons at 60.7 (C-2) and 65.9 (C-3) ppm are the -CH 2 -carbons of HO-CH 2 -CH 2 -OCOO − [20,21]. Similar carbon peaks could also be found in the Mukesh and co-authors' paper [22].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The 1 H- 13 C HMBC suggested that the carbon C-4 should be the carbonyl carbon of the carbonate formed by CO 2 and EG. The carbons at 60.7 (C-2) and 65.9 (C-3) ppm are the -CH 2 -carbons of HO-CH 2 -CH 2 -OCOO − [20,21]. Similar carbon peaks could also be found in the Mukesh and co-authors' paper [22].…”
Section: Resultssupporting
confidence: 64%
“…The peak at 1635 cm −1 is associated with the combined C=O stretching band of carbonate and carbamate species, and the peak at 1573 cm −1 corresponds to COO − asymmetric stretching of carbamate -NHCOO − . The new peak at 1296 cm −1 is ascribed to the stretching band of RO-COO − [21]. The FTIR results suggested again that both carbonate and carbamate species are formed after CO 2 capture.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, some special DESs able to react with CO 2 also exist. An example is the [EMIM][2-CNpyr]: EG (1:0.5-1.10) solvent studied by Lee and coworkers [145]. The authors carried out a detailed reaction mechanism investigation, pointing out that carbonate formation is the dominant reaction while carbamate formation is minimal.…”
Section: Co 2 Capture Deep Eutectic Solventsmentioning
confidence: 99%
“…The band at 1639 cm À1 relates to the CQO stretching of the EG-based carbonate, 33,36 and the band at 1282 cm À1 is from the O-C-O stretch. 29 Nevertheless, the CQO stretching band of the phenol-based carbonates cannot be observed in the FTIR spectra of [DBUH][Car] : EG (1 : 2) after absorption, which falls around 1615 cm À1 . 34,35 Therefore, the FTIR results confirm again that CO 2 is attached to EG, not to the [Car] À anion.…”
mentioning
confidence: 99%